Bullying sebagai Arena Kontestasi Kekuasaan di Kalangan Siswa SMA Jakarta - Prisanti Windi Andini; Amirudin Amirudin; Mulyo Hadi Purnomo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
Bullying among students, especially high school students are still common. Acts of violence in schools involve both senior and junior. The seniors’ role of displaying seniority is to teach the juniors manners and discipline. But there are many seniors who abuse the terms of seniority by acting arbitrarily to their juniors. This article will explain how bullying can be considered as a field of power contestation. This study uses several techniques of ethnographic methods, namely, direct observation, interview, and literature. Researchers used indirect observation because informants are reluctant to commit acts of violence when there are other people outside their group. Based on the results of the research, capital are at stake for the actors to reach the prize, such as honor, fame, and material. Bullying behavior that occurs in SMA E Jakarta continues because of an understanding that they have to continue what has been instilled by their seniors before, such as the rules for class X are always imposed from year to the next one.